2013
DOI: 10.1016/j.jocrd.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of explicit and implicit threat overestimation in contamination fear

Abstract: We examined the predictive validity of explicit and implicit measures of threat overestimation in relation to contamination-fear outcomes using structural equation modeling. Undergraduate students high in contamination fear (N = 56) completed explicit measures of contamination threat likelihood and severity, as well as looming vulnerability cognitions, in addition to an implicit measure of danger associations with potential contaminants. Participants also completed measures of contamination-fear symptoms, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…The limited evidence of an involvement of implicit processes is similar to the finding by Green and Teachman (2013) that implicit threat overestimation was only marginally related to behavioural avoidance, while explicit threat overestimation significantly predicted subjective distress and contamination-fear symptoms. However, it is inconsistent with other findings that only examined the role of implicit factors (Nicholson & Barnes-Holmes, 2012; Nicholson et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The limited evidence of an involvement of implicit processes is similar to the finding by Green and Teachman (2013) that implicit threat overestimation was only marginally related to behavioural avoidance, while explicit threat overestimation significantly predicted subjective distress and contamination-fear symptoms. However, it is inconsistent with other findings that only examined the role of implicit factors (Nicholson & Barnes-Holmes, 2012; Nicholson et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…The issue of shared method variance needs to be acknowledged between the selfreport questionnaires of disgust and threat overestimation, and the self-report nature of subjective contamination fear and contamination-fear OC tendencies. This issue was also raised by Green and Teachman (2013) and deemed not to be a concern in their study. Similarly, in the current study, given the differential involvement of explicit disgust and explicit threat overestimation depending on the contaminant, and their prediction of behavioural avoidance, which does not rely on self-report, it is unlikely that shared method variance explains the strong predictive value of these explicit measures.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, other research has not found the anticipated between-group effects on implicit measures of OC-relevant cognition (e.g., self + aggression: Cludius et al 2017) or relationships between self-reported symptoms and implicit measures (e.g., self + immoral, self + dangerous, unwanted thoughts + important: Teachman & Clerkin 2007, Teachman et al 2006. Interestingly, studies using implicit measures other than the IAT to evaluate OC-relevant cognition have been more successful at confirming hypotheses (e.g., Brief IAT: Green & Teachman 2013). Research with other non-IAT paradigms suggests that implicit OC-relevant cognition is likely associated with a range of OC-relevant variables, including scrupulosity (GNAT associations: Pirutinsky et al 2015), excessive responsibility and overestimation of threat (IRAP: Nicholson et al 2013), and contamination fear and avoidance behavior (IRAP: Nicholson et al 2014).…”
Section: Obsessive-compulsive Disorder: Empirical Evidencementioning
confidence: 98%
“…A great number of previous studies indicate that negative emotionality, maladaptive cognitive style, and low levels of optimism are associated with the risks of negative psychological impacts [ 9 , 19 , 20 ]. People who overestimate threats or lack tolerance of uncertainty in pandemics can become highly worried and anxious during pandemics [ 21 ]. Perception of stress and helplessness arising from the stressful situations of the epidemic could have direct effects on the mental health of individuals and lead to prevalence of depression and anxiety [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%